PENGETAHUAN IBU HAMIL TENTANG HYPNOBIRTHING DI BPM SITI AMINAH SUKOHARJO - Ana Yuliana; Oki Dameria (OVUM : Journal of Midwifery and Health Sciences, 2021)
Efforts are being made to reduce maternal and neonatal morbidity and mortalitywith Making Pregnancy Safer (MPS) which expresses the vision that pregnancyand childbirth in Indonesia are safe, and those born alive and well. Thehypnobirthing method is useful for reducing pain and facilitating the deliveryprocess because this method always provides positive energies for pregnantwomen. Hypnobirthing is the best way to neutralize and reprogram(reprogramming) negative recordings in the subconscious mind with positiveprogramming.This study uses a descriptive quantitative type of accidental sampling with 32pregnant women as respondents.Based on the data analysis, it was found that the level of knowledge abouthypnobirthing was in the good category of 2 people (6.25%), 18 people withsufficient knowledge (56.25%), and 12 people with less knowledge (37.5%).The conclusion of the study shows that the level of knowledge of pregnant womenabout hypnobirthing is in the sufficient category.